2019
DOI: 10.3389/fpsyg.2019.01544
|View full text |Cite
|
Sign up to set email alerts
|

Pre-specified Anxiety Predicts Future Decision-Making Performances Under Different Temporally Constrained Conditions

Abstract: In real-life circumstances, people occasionally require making forced decisions when encountering unpredictable events and situations that yield socially and privately unfavorable consequences. In order to prevent future negative consequences, it is beneficial to successfully predict future decision-making behaviors based on various types of information, including behavioral traits and/or psychological states. For this prospective purpose, the present study used the Iowa Gambling Task, which simulates multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…As confirmed in Figure 1 , the net scores showed no significant differences between the blocks ( F (4, 60) = 1.128, p = 0.352, partially ( p ) η 2 = 0.070); that is, the temporal pressure and enhanced information ambiguity attenuated the development of risk-avoidance preference (gradual increase in net scores). This result is consistent with previous finding [ 23 ], which observed lower risk-avoidance under temporal pressure and information ambiguity compared to previous observations of IGT.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…As confirmed in Figure 1 , the net scores showed no significant differences between the blocks ( F (4, 60) = 1.128, p = 0.352, partially ( p ) η 2 = 0.070); that is, the temporal pressure and enhanced information ambiguity attenuated the development of risk-avoidance preference (gradual increase in net scores). This result is consistent with previous finding [ 23 ], which observed lower risk-avoidance under temporal pressure and information ambiguity compared to previous observations of IGT.…”
Section: Resultssupporting
confidence: 94%
“…Previous studies observed lower risk-avoidance behavior under information ambiguity conditions [ 21 , 22 ], and adding temporal pressure to information ambiguity also induced this tendency [ 23 ]. Following these studies, our analysis of Experiment 1 also employed a net score as the index of risk-avoidance preference.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations